VD_FINDINFO HC / 2019 / 90 vom 13. Februar 2019 - VD Tribunal cantonal (2019)
OBLIGATION D'ENTRETIEN, MAJORITÉ{ÂGE}, ENFANT | 276 al. 1 CC, 277 al. 2 CC, 285 al. 1 CC, 106 al. 1 CPC (CH), 312 al. 1 CPC (CH)